Bilateral musculocutaneous nerve palsy from strength training - Matz, S. O.; Nibbelink, G. (The Physician and Sportsmedicine, 2004)
Musculocutaneous nerve palsy resulting from strenuous weight training is a rare condition characterized by biceps atrophy or weakness. It usually affects the dominant side, but the authors describe an 18-year-old football player who developed the condition bilaterally after weight lifting--a presentation not found in the literature. Clinicians should keep the diagnosis in mind for active patients who perform repetitive biceps curls. When other neurologic conditions have been clinically ruled out, electrodiagnostic testing can confirm the diagnosis. Musculocutaneous nerve palsy typically resolves when weight training routines are modified to reduce intensity and biceps curls are eliminated for at least 3 months.